PERSONALITY-MEDIATED DIFFERENCES IN COPING BEHAVIOR AS PRECURSORS OF THE SUBJECTIVE WELLBEING - Arshava, Iryna; Nosenko, Eleonora; Nosenko, Dina (European Scientific Journal, ESJ, 2014)
The phenomenon of the subjective well-being (SWB), which is used in the contemporary personality research as the correlate of the key notion of the lay theories of happiness, is claimed to be determined predominantly by neuroticism, since the demographic personality factors, widely investigated in this context, appeared to have only about 10 % effect on happiness. The objective of this study was to examine the hypothesis of the existence of a hierarchy of the personality precursors of the subjective well-being and mental health continuum (MHC), which were verified through the mediating effect on the choice of the different forms and strategies of coping behavior. Using the statistical methods of the correlational, factor and cluster analysis, it was found out on a sample of a 64 university undergraduates, that SWB and MHC are determined by the hierarchy of personality precursors, the key role among which is played by ego-involvement (strive to self-evolution), ego-identity (self-esteem and belief in self-efficacy), while neuroticism had significant negative correlations only in one out of three factors singled out in the sample. It was concluded that the higher are the levels of ego-involvement and ego-identity, the more diverse is the repertoire of the constructive coping strategies and forms of coping behavior. The phenomenon of self-handicapping, conceptualized in this research as the form of nonconstructive proactive coping, appeared to be significantly lower in clusters with high egoidentity and ego-involvement. Thus, its status as a non-constructive coping strategy was confirmed.